Pedagogical intervention based on the TPACK model to develop emergent literacy skills in preschool education in Chile - Fernández-Chávez, Carolina; Domínguez-Ramírez, Paola; Salcedo-Lagos, Pedro; Valenzuela, Bárbara; Fuentealba, Valeria (Journal of Education and Learning (EduLearn), 2026)
The use of information and communication technologies (ICTs) in education has become necessary due to the various global challenges faced in this area. This study aimed to evaluate the effect of a pedagogical intervention based on the technology pedagogical content knowledge (TPACK) model that integrates ICTs to develop phonological awareness and letter recognition in kindergarten children. The methodology supporting this research is quantitative; the phonological awareness evaluation test (PAET) and letter recognition test (LRT) were administered. The sample consisted of 118 kindergarten children, 59 in the intervention group, and 59 in the control group. The information was analyzed using descriptive statistics, a paired t-test, and the non-parametric Mann-Whitney U test. The results show significant differences between the two groups, with the intervention group achieving better results. The TPACK model’s guidance for implementing the intervention, professional development in using and integrating ICTs in the classroom, and collaborative work among professionals are highlighted.